2020
DOI: 10.3389/fgene.2020.589076
|View full text |Cite|
|
Sign up to set email alerts
|

Identification of mRNAs and lncRNAs Involved in the Regulation of Follicle Development in Goat

Abstract: Follicular development and maturation has a significant impact on goat reproductive performance, and it is therefore important to understand the molecular basis of this process. The importance of long non-coding RNAs (lncRNAs) in mammalian reproduction has been established, but little is known about the roles of lncRNAs in different follicular stages, especially in goats. In this study, RNA sequencing (RNA-seq) of large follicles (>10 mm) and small follicles (<3 mm) of Chuanzhong black goats was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…In recent years, many studies of the mechanisms of prolificacy in goats have focused on candidate genes and their regulators, such as miRNAs, transcription factors, and varieties of regulated pathways. All these factors form a network of many interactions in vivo that regulate the goat reproduction trait ( Lu et al, 2020 ; Zhao et al, 2020 ). The genes GDF9, Smad2, BMP15, and BMP4, and the transcription factor Sox9 are involved in kidding number and increased ovulation rate, and are proven to be crucial for the reproductive performance of goats ( Hanrahan et al, 2004 ; Lai et al, 2016 ; Chinmoy et al, 2017 ; He et al, 2020 ; Wang et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, many studies of the mechanisms of prolificacy in goats have focused on candidate genes and their regulators, such as miRNAs, transcription factors, and varieties of regulated pathways. All these factors form a network of many interactions in vivo that regulate the goat reproduction trait ( Lu et al, 2020 ; Zhao et al, 2020 ). The genes GDF9, Smad2, BMP15, and BMP4, and the transcription factor Sox9 are involved in kidding number and increased ovulation rate, and are proven to be crucial for the reproductive performance of goats ( Hanrahan et al, 2004 ; Lai et al, 2016 ; Chinmoy et al, 2017 ; He et al, 2020 ; Wang et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Most of the lncRNAs were located close to protein‐coding genes (Nam & Bartel, 2012; Ulitsky et al, 2011; Vallot et al, 2013), indicating that these lncRNAs have synergistic relationships with mRNAs. The sequence length and exon number of lncRNAs and mRNAs in the DFs and SFs of granulosa cells have a similar pattern to those in the large and small follicles of goats (Zhao et al, 2020). The ORF length of lncRNAs and mRNAs mainly ranges from 0 to 400 bp.…”
Section: Discussionmentioning
confidence: 81%
“…Several studies based on global gene expression analyses have already detected differential gene expression in follicles at different developmental stages of goats. CDO1 and TC2N were upregulated in large follicles and might potentially participate in the regulation of follicular maturation in goats (Zhao et al, 2020). Of particular interest was that the expression of CDO1 and TC2N was higher in the DFs than in the SFs of granulosa cells, which have not been identified in the context of follicular development and maturation before.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several studies have confirmed that lncRNAs play key regulatory roles in goat reproduction [ 28 , 65 ]. Thus, the lncRNA–target gene (DEG) interaction network was constructed.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, numerous works have proved that lncRNA expression can lead to early germ cell formation and embryo implantation, and the process of mammalian animal reproduction [ 24 , 25 ]. In goats, lncRNAs have been identified in the ovaries, uterus, and germ cells [ 26 , 27 , 28 ] and might regulate the oogenesis and maturation, embryo implantation, and oocyte follicle development. Wang et al analyzed lncRNAs and mRNAs in goat perirenal adipose tissues and found that 4519 lncRNAs and 5212 mRNAs were potentially in trans-regulatory relationships and that the target genes of lncRNAs were associated with brown to white adipose tissue transformation [ 29 ].…”
Section: Introductionmentioning
confidence: 99%